Polycaprolactone Scaffolds Fabricated via Bioextrusion for Tissue Engineering Applications - Marco Domingos; Dinuccio Dinucci; Stefania Cometa; Michele Alderighi; Paulo Jorge Bártolo; Federica Chiellini (International Journal of Biomaterials)
The most promising approach in Tissue Engineering involves the seeding of porous, biocompatible/biodegradable scaffolds, with donor cells to promote tissue regeneration. Additive biomanufacturing processes are increasingly recognized as ideal techniques to produce 3D structures with optimal pore size and spatial distribution, providing an adequate mechanical support for tissue regeneration while shaping in-growing tissues. This paper presents a novel extrusion-based system to produce 3D scaffolds with controlled internal/external geometry for TE applications.The BioExtruder is a low-cost system that uses a proper fabrication code based on the ISO programming language enabling the fabrication of multimaterial scaffolds. Poly(ε-caprolactone) was the material chosen to produce porous scaffolds, made by layers of directionally aligned microfilaments. Chemical, morphological, and in vitro biological evaluation performed on the polymeric constructs revealed a high potential of the BioExtruder to produce 3D scaffolds with regular and reproducible macropore architecture, without inducing relevant chemical and biocompatibility alterations of the material.